"Spatial Distribution of Forest Reserves and Sawmills in Oyo State, Nigeria" (2017)
Geographic Information System (GIS) is a veritable tool for spatial analysis in forestry. The proximity to forest reserves has been considered one of the major factors affecting the spatial distribution of wood-based industries. However, information on number of sawmills and spatial distribution of both the forest reserves and sawmill in Oyo Sate is lacking. Hence, this study employed GIS to develop spatial distribution map of forest reserves and sawmills in Oyo State, Nigeria. The secondary data used in this study included sketch maps and high-resolution satellite imagery of all the forest reserves in Oyo State as well as the shapefile of the State. The primary data included the coordinates of locations of all the sawmills’ location in all the four forestry zones (Ibadan, Oyo, Shaki and Ogbomosho) in the state and coordinates of some bench-mark places within each forest reserve that could easily be identified on ground. Interview guide was used to obtain information on factors responsible for the location of each sawmill. The sketch maps were georeferenced using the coordinates of the bench-mark places and the area covered by forest reserves were digitized. This was superimposed on the satellite imageries and also vectorized. The coordinates of sawmill locations were used to develop spatial distribution map for the sawmills. The shapefile of forest reserves and the point coordinates of the sawmills were superimposed on the shapefile of Oyo State in layers to produce a spatial distribution prediction surface for both the forest reserves and the sawmills in the study area. The mean distance from each sawmill to the forest was determined. This procedure was used to obtain Average Transport Distance (ATD) for local government and finally for forestry zones. It was observed that forest reserves in Oyo State covered a total of 342,461 ha of land which accounted for 12.92% of the total land area of the state. Opara forest reserve recorded the highest area of land (248,640 ha), accounting for about 72.60% of the total land area of forest reserves in the state while the least was Olokemeji forest reserve (75.11 ha), accounting for about 0.02%. About 135 sawmills were recorded in all the forestry zones in Oyo State. Sawmills in Oyo forestry zone is significantly higher than Ibadan zone. ATD was highest in Ibadan forestry zones (12.55 km) with corresponding lowest percentage (3.70 %) of sawmills. Oyo Forestry Zone accounted for about 56.30 % of the total number of sawmills in the state with the least ATD of 4.02 km. Availability of electricity and nearness to source of raw material favoured sawmills location in Oyo and Shaki forestry zones. Spatial distribution of sawmills was more influenced by constant supply of electricity and nearness to free forest areas than the presence of forest reserves.